Microstructure evolution and mechanical properties of wire-feed electron beam additive manufactured Ti-5Al-2Sn-2Zr-4Mo-4Cr alloy with different subtransus heat treatments. (October 2020) - Zhang, Guodong; Xiong, Huaping; Yu, Huai; Qin, Renyao; Liu, Wei; Yuan, Hong
Abstract: Wire-feed electron beam additive manufacturing (EBAM) is a promising manufacturing process for fabrication large-scale, fully dense and near net shape metallic components. However, limited knowledge is available on the wire-feed EBAM process of titanium alloys. In this work, the Ti-5Al-2Sn-2Zr-4Mo-4Cr near β titanium alloy sample was fabricated by the EBAM process and the effect of subtransus solution and aging treatment on the microstructure evolution and mechanical properties was investigated. The results reveal that the volume fraction of the primary α decrease dramatically from 48.6% to 8.9% with increasing the solution temperature from 750 °C to 850 °C. The ultimate tensile strength and yield strength increase monotonously with increasing of the solution temperature, while the elongation and reduction of area change conversely. The thickness of the secondary α (αS ) increases significantly from 28.6 nm to 120.1 nm with the aging temperature increasing from 550 °C to 710 °C. The volume fraction and thickness of αS are sensitive to the aging temperature and strongly influence the mechanical properties. The quantitative relationship between the microstructure and mechanical properties was established. As a good result, the tensile properties of the post-deposition heat treated alloy at 400 °C can meet the standard requirements for wrought counterpart. Graphical abstract: Unlabelled Image Highlights: Wire-feed electron beam additive manufacturing of Ti-5Al-2Sn-2Zr-4Mo-4Cr near β titanium alloy was conducted. The volume fraction and thickness of α phases can be tailored by adjusting the temperature of solution and aging treatment. 400 °C tensile properties of the post-deposition heat treated alloy can meet the requirements for wrought counterpart. Quantitative relationship between the phase volume fraction, phase size and mechanical properties was firstly established.